37 Clinical Profile and Management of Aerodigestive Foreign Bodies: A Prospective Observational Study - Sheetal Kumari; Neeru Bala; Ajaz Ul Haq; Parmod Kalsotra (Dr. Annil Mahajan, 2022)
Objective : Foreign bodies in aerodigestive tract are one of the common emergencies in ENT. A suspicious mind with meticulous history taking may save many lives. The study is about the experience of aerodigestive tract foreign bodies in tertiary care hospital. Study Design and Methods: We carry a Observational study of about 352 patients who came or were referred to our department from August 2017 to August 2020. FB involving different parts of the aero digestive tract were included in the study. The site, side, symptoms and radiographic findings were recorded for each patient. Different procedures were used for retrieval of various FB at different locations.Majority of these procedures were performed under general anesthesia. Results : A total of 352 cases of aerodigestive foreign bodies were seen comprising of 224 males and 128 females in a ratio of 1.7:1. Age ranged from 6 months to 78 years. The group most at risk of aero digestive foreign bodies are those aged between 0 to 5 years. Common foreign bodies were coins, vegetative foreign bodies and parts of toys in children and meat bone and meat bolus and denture in adults. Conclusion: Aerodigestive foreign bodies are a common occurrence especially in the pediatric age group. Early detection and removal can forestall